Knowledge with wisdom in postgraduate studies and supervision: Epistemological and institutional concerns and challenges - Bitzer , EM (South African Journal of Higher Education, 2011)
Publications about postgraduate studies and the supervision address issues and concerns such as supervisory orientations and strategies, ways to handle postgraduate students, challenging postgraduate education practices, factors related to success in postgraduate studies, the benefits of advanced studies, transition to independent research and researcher identity development. However, few studies, if any, address the epistemological and institutional contexts and their implications in which master’s and doctoral studies are conducted and supervised. In attempting to narrow this conceptual gap, this article reminds readers that before the advent of modern science, humans lacked the scientific and technological means to effect large-scale damage to life and the environment. At present, however, due to unprecedented powers created by knowledge and science a lack of wisdom has become a major threat; promoted, among other things, by the way in which postgraduate research and supervision are undertaken. I therefore argue that promoting wisdom does not oppose promoting and generating knowledge. Similarly, if the transformation of universities in modern society is characterised by the search for and exploration of wisdom, it can do justice to the continuity of the university’s original ideals and might benefit postgraduate studies and their supervision.